Quality of coffee submitted to different temperatures, air flow and pre-drying period - Borém, Flavio Meira; Ribeiro, Deise Menezes; Pereira, Rosemary Gualberto Fonseca Alvarenga; Rosa, Sttela Dellyzete Veiga Franco da; Morais, Augusto Ramalho de (Coffee Science - ISSN 1984-3909, 2007)
The objective of the present work was to evaluate the effect of different temperatures, air flow and pre-drying periods on yard in the quality of parchment coffee (Coffea arabica L.). Coffee beans were submitted to two periods of pre-drying: 1 and 3 days. After these periods, the product was submitted to drying in experimental dryers with fixed layer using two air flows (20 and 30 m3min- 1m-2) and three temperatures in the mass of beans (40, 45 and 50 ºC) with three replicates. Sensorial and chemical analyses were carried out for the characterization of coffee quality. The results indicate that increasing the pre-drying period and air flow and decreasing temperature contribute to the decrease of values of the electric conductivity and potassium leaching of the coffee beans; the total sugar content reduces significantly only with the elevation of the drying temperature for the beans submitted to 1 day of predrying; for the combined drying, the parchment coffee should be kept at least three days on the yard under appropriate drying conditions and the temperature should not be more than 40 ºC in the complementary drying to guarantee the best coffee quality.